Morphological features of healing in experimental cortical layer defect of long bone upon condition of β-tricalcium phosphate implantation - Korenkov, Olexiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Objective: To compare the healing process in the defect of compact bone tissue after implantation of osteoplastic material ChronOS ™ with restoration of unfilled defect. Methods: An experiment was conducted on 24 white male rats. In the middle third of the femoral shaft we created hole defect with 2.5 mm diameter toward the medullary canal, and we left it unfilled (control, group I) or filled with osteoplastic material ChronOS ™ (group II). Fragments of injured bones were examined after 15 and 30 days by means of methods of light microscopy with morphometry and scanning electron microscopy. Results: It was found that the material ChronOS ™ did not induce any inflammatory response, and in the implantation area adjacent to the maternal bone there were gaps with typical osteocytes, and in micropores of ChronOs ™ - osteogenic cells with small foci of osteogenesis suggesting the biocompatibility and osteotropism of this material. In all terms of observation there were revealed some signs of just desmal osteogenesis which indicates the presence in defects of bone and connective tissue in both groups of the animals on. Bone tissue of regenerate in the control group presented with large and small loop meshwork of trabecular bone. In group II animals the newly formed bone tissue repeated the shape of pores of the implant has and contained a large amount of osteoblasts and osteocytes. On the 30th day in defects of animals of both groups we found areas of bone tissue approaching in structure to maternal bone. Material ChronOs ™ subjected to resorption and replaced by bone and connective tissues. Their relationship on the 15th day of the experiment was (39,75 ± 2,85) / (41,1 ± 1,87) / (19,14 ± 1,2)%, on the 30th day - (26,67 ± 1,15) / (54,53 ± 2,6) / (18,8 ± 0,8)%.